An adaptive overcurrent protection system applied to distribution systems. (January 2020) - Nascimento, Jamile P.; Brito, Núbia S.D.; Souza, Benemar A.
Abstract: In this paper, an innovative adaptive directional overcurrent protection system for electric power distribution systems with respect to distributed generation is proposed. The proposed system supervises network topology based on the monitoring functionality of numerical relays. The system detects any changes in the configuration and recalculates the directional overcurrent protection settings by using a microgenetic algorithm. The proposed system was evaluated for several operating scenarios and insertion levels of distributed generation, and then compared with both conventional and adaptive protection systems by means of a traditional genetic algorithm. The results showed that the performance of the proposed system is superior to the other two methods in terms of both speed and selectivity. This shows that this is a promising proposal for the protection of modern electric power distribution systems.